2008
DOI: 10.1097/mlr.0b013e31816c43d9
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Status of Patients Admitted to Specialty Cardiac and Competing General Hospitals

Abstract: Patients with more generous insurance are significantly more likely to gain admission to specialty hospitals. Alternatively, we found no evidence that specialty hospitals preferentially transfer patients with less generous insurance who are admitted. Overall, these findings suggest that specialty hospitals may contribute to segregation of the healthcare system along socioeconomic lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…Data elements include patient demographics, primary and secondary diagnoses as captured by ICD-9-CM codes, insurance type (categorized as Medicare, Medicaid, private, uninsured, no charge, other), and discharge disposition (categorized as routine, short-term hospital, skilled nursing facility, intermediate care facility, another type of facility, home health care, against medical advice, or died). The NIS has been used extensively in prior health services research [15]. Weights for the NIS are provided by AHRQ to allow researchers to calculate nationally representative estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Data elements include patient demographics, primary and secondary diagnoses as captured by ICD-9-CM codes, insurance type (categorized as Medicare, Medicaid, private, uninsured, no charge, other), and discharge disposition (categorized as routine, short-term hospital, skilled nursing facility, intermediate care facility, another type of facility, home health care, against medical advice, or died). The NIS has been used extensively in prior health services research [15]. Weights for the NIS are provided by AHRQ to allow researchers to calculate nationally representative estimates.…”
Section: Methodsmentioning
confidence: 99%
“…To the extent that patients with similar sociodemographics (and risk for complications) cluster within hospitals, [27][28][29] certain hospitals could benefit by having a relatively low-risk TKA population and see profits from TKA soar; alternatively, other hospitals with a predominantly higher risk TKA population could see TKA as financially detrimental based upon geographic location and catchment area alone. 30 There is certainly reason to be concerned that episode-of-care payments could provide additional incentive for hospitals and physicians to select lower risk patients while avoiding higher risk patients. 31 Of course if bundled payment amounts were adjusted to reflect each hospital's particular patient mix, such problems could be alleviated to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that there was a higher proportion of transfers accepted into teaching hospitals, greater proportion of admissions on the weekend, and relatively fewer elective procedures performed. While NTH treated a greater proportion of lower socioeconomic status patients compared to teaching hospitals, socioeconomic factors influence outcomes, 20 and thus sicker patients treated at certain hospitals may reflect a different patient population based on nonmedical parameters, 21 and require further investigation. Since 2008, when centers were performing endovascular repair as feasible, and several reports described their long-term experience, the learning curve for transcatheter procedures seems to have stabilized.…”
Section: Discussionmentioning
confidence: 99%